0504 Mortality Risk Associated with Mild-to-Moderate Sleep Apnea is Modified by Age. (12th April 2019) - Vgontzas, Alexandros N; Fernandez-Mendoza, Julio; He, Fan; Liao, Duanping; Li, Yun; Bixler, Edward O
Abstract: Introduction: Mild-to-moderate sleep apnea (OSA) is highly prevalent in the general population but its association with morbidity and mortality is not well-established. We examined the association between mild and moderate OSA and all-cause mortality in a large random general population sample. Methods: The Penn State Adult Cohort, a random general population sample of 1741 men and women studied in the sleep laboratory with 8-hours polysomnography at baseline and followed-up for 19.2 ± 5.2 years for all-cause mortality. Mild OSA was defined as an apnea/hypopnea index (AHI) of 5 to 14.9 events/hour, while moderate OSA as an AHI of 15 to 29.9 events/hour. Cox proportional hazards regression was used to estimate all-cause mortality adjusted for race, sex, BMI, smoking, hypertension, diabetes, heart problems and stroke at baseline. Results: All-cause mortality risk was significantly increased in the mild-to-moderate OSA group (HR= 1.28, 95%CI=1.04-1.57, p=0.019). The risk of mortality was 1.4-fold (95% CI = 1.04-1.98, p = 0.027) in young and middle-aged adults (20-59y) with mild-to moderate OSA, whereas it was negligible in older adults (>60y) with mild-to moderate OSA (HR = 1.14, 95% CI = 0.87-1.49, p = 0.336). Conclusion: Mild-to-moderate sleep apnea is associated with significant all-cause mortality risk but the strength of the association decreases markedly with age. These findings are in line with previous findings that the association of mild-to-moderate OSA with cardiometabolic risk is modified by age and suggests that OSA in older adults is a distinctly different phenotype than in the young and middle-aged. Support (If Any): NA